2017
DOI: 10.1007/s00256-017-2792-5
|View full text |Cite
|
Sign up to set email alerts
|

T2 signal intensity as an imaging biomarker for patients with superficial Fibromatoses of the hands (Dupuytren’s disease) and feet (Ledderhose disease) undergoing definitive electron beam irradiation

Abstract: MRI is valuable for evaluating patients undergoing electron beam therapy for superficial fibromatoses: higher pretreatment T2 intensity may predict benefit from radiotherapy. T2 hypointensity may be a better marker than size for therapeutic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Five studies reported the use of US or MRI to evaluate different operative and non-operative treatment modalities (Table 7). Three studies used US or MRI to follow-up non-invasive treatment [3638]. In the first study, US was used to follow-up cross-frictional treatment of a patient with early stage DD, which is a therapy that aims to reduce contracture by stretching the Dupuytren tissue [36].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies reported the use of US or MRI to evaluate different operative and non-operative treatment modalities (Table 7). Three studies used US or MRI to follow-up non-invasive treatment [3638]. In the first study, US was used to follow-up cross-frictional treatment of a patient with early stage DD, which is a therapy that aims to reduce contracture by stretching the Dupuytren tissue [36].…”
Section: Resultsmentioning
confidence: 99%
“…A significant decrease in size was detected from pre-injection to 6 months follow-up and to the final follow-up. In the third study, MRI was used to follow-up size and signal intensity of superficial fibromatoses of the hands and feet in patients undergoing electron beam therapy (EBT) [38]. Intensity decreased significantly, which was attributed to progression from the proliferative to the residual stage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On MRI, plantar fibromas are seen as small to medium-sized fusiform-shaped nodule or clustered nodules attached to and extending along the plantar aponeurosis ('fascial tail sign'), usually the medial cord. T2 hyperintense (relative to muscle) lesions with avid contrast enhancement tend to be actively growing lesions, containing proliferative fibroblastic tissue, that are more responsive to electron beam irradiation therapy, while T2 isointense or hypointense lesions with poor enhancement tend to be quiescent lesions, containing mature collagenous tissue (27) .…”
Section: Plantar Fibromatosis (Ledderhose Disease)mentioning
confidence: 99%